PSYCHOLOGICAL VIEWS OF TOURISTS IN TOURISM - Fotima Saydullaeva , Ph.D; Ergashev Shokhrukh Jamolovich (European Science Publishing, 2024)
The article discusses the results of a practical study of the psychological aspects of tourism. The importance of the attitude of a person to the places he visits, as well as individual personal characteristics of tourists, is emphasized. These relationships include three main components: cognitive, emotional-motivational and behavioral. The personal aspect of the psychological content of tourism includes aspects such as value orientations and self-awareness characteristics.
Keywords: psychological content of tourism, individual's attitude to geographical space, image of tourist place, psychological functions of tourism, emotions, subjective vitality, behavioral models